Are Emotional Dispositions Central to Virtue? - Rossi, Mauro (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
In this article, I offer some comments on chapter 10 of Christine Tappolet’s book Philosophy of Emotion: A Contemporary Introduction, the chapter entitled “Ethics and the Emotions”. After presenting the main theses that Tappolet defends in this chapter, I consider some possible replies that her opponents might offer.